HYPONATREMIA: IS IT RELATED TO THE SEASONS? Hyponatremia and Seasons - Altuntaş, Atila (Journal of Medical Biochemistry, 2021)
Objectıve: Hyponatremia is a common electrolyte disorder in inpatients and related with morbidity and mortality. In this study we aimed to examine whether there is a relationship between incidence of hyponatremia among patients hospitalized in our nephrology department and the seasons.Material and Methods: Inpatients in our Nephrology Department between 2012-2015 were retrospectively analyzed. Patients with serum sodium levels below 135 mEq / L were included in the study. Hyponatremia incidence was calculated as the proportion of inpatients with low sodium levels in a season to total number of inpatients in the same season.Results: Out of 1950 inpatients in four-years period, 509 were found to have hyponatremia (26.1%). Mean serum sodium level of the patients was 129.7±4.7 mEq/L. Hyponatremia incidences in autumn, winter, spring and summer were found to be 28.7%, 15.4%, 20.4% and 36.6% respectively. Comparing the incidence of hyponatremia in patients hospitalized in winter and summer seasons, there was a significantly higher incidence of hyponatremia in summer (p
Keywords: Hyponatremia, season, humidity, temperature, renal failure.